Estimation of the Eddy-Diffusion Coefficients in the Plasma Sheet Using Themis Satellite Data - Stepanova, M (2011)
We have studied the turbulent processes in the central plasma sheet using the tailward alignments of THEMIS satellites. Fluctuations of the plasma bulk velocity and corresponding eddy-diffusion coefficients were calculated using the simultaneous data obtained by THEMIS satellites situated inside the central plasma sheet between approximately 5 and 30 Earth s radii. The instantaneous profiles of eddy-diffusion coefficients show an increase with distance from the Earth in the tailward direction. This result agrees with previous statistical studies, and it is relevant for the understanding of the dynamics of the turbulent plasma sheet. © 2011 Elsevier Ltd.